Progenitor death drives retinal dysplasia and neuronal degeneration in a mouse model of ATRIP-Seckel syndrome - Gabriel E. Matos-Rodrigues; Pedro B. Tan; Maurício Rocha-Martins; Clara F. Charlier; Anielle L. Gomes; Felipe Cabral-Miranda; Paulius Grigaravicius; Thomas G. Hofmann; Pierre-Olivier Frappart; Rodrigo A. P. Martins (The Company of Biologists, 2020)
Seckel syndrome is a type of microcephalic primordial dwarfism (MPD) that is characterized by growth retardation and neurodevelopmental defects, including reports of retinopathy. Mutations in key mediators of the replication stress response, the mutually dependent partners ATR and ATRIP, are among the known causes of Seckel syndrome. However, it remains unclear how their deficiency disrupts the development and function of the central nervous system (CNS). Here, we investigated the cellular and molecular consequences of ATRIP deficiency in different cell populations of the developing murine neural retina. We discovered that conditional inactivation of Atrip in photoreceptor neurons did not affect their survival or function. In contrast, Atrip deficiency in retinal progenitor cells (RPCs) led to severe lamination defects followed by secondary photoreceptor degeneration and loss of vision. Furthermore, we showed that RPCs lacking functional ATRIP exhibited higher levels of replicative stress and accumulated endogenous DNA damage that was accompanied by stabilization of TRP53. Notably, inactivation of Trp53 prevented apoptosis of Atrip-deficient progenitor cells and was sufficient to rescue retinal dysplasia, neurodegeneration and loss of vision. Together, these results reveal an essential role of ATRIP-mediated replication stress response in CNS development and suggest that the TRP53-mediated apoptosis of progenitor cells might contribute to retinal malformations in Seckel syndrome and other MPD disorders. This article has an associated First Person interview with the first author of the paper.